The The Influence of Profitability, Leverage, Sales Growth, and Book Tax Differences on Corporate Tax Avoidance - Dwi Hapsoro, Dian; Karina, Dhiya Syifa; Darmawan, Muhammad; Wahono, Puji; Pahala, Indra (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This research aims to investigate the influence of profitability, leverage, sales growth, and book-tax differences on tax avoidance in the food and beverage industry. The research sample consists of companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. Using multiple regression analysis, this study examines the relationship between the dependent variable, which is the cash effective tax rate (CETR), and the independent variables, profitability (ROA), leverage (DER), sales growth, and book-tax differences. The results show that profitability has a negative impact on tax avoidance, leverage has a negative impact on tax avoidance, sales growth contributes positively to tax avoidance, and book-tax differences have a positive effect on tax avoidance. The influence of profitability, leverage, sales growth, and book-tax differences on tax avoidance is 37.5%, as indicated by the R-Square value of 0.375 for CETR. This indicates that there are 62.5% other factors not identified in this research that also affect tax avoidance. This research is important for policymakers as it shows that although factors such as profitability and leverage play a role in tax avoidance, there are many other factors that must also be considered. Therefore, further research is recommended to include additional variables and involve data from companies in other sectors to gain a broader perspective. This can help in formulating more effective policies in controlling tax avoidance across various industries. The findings provide significant insights into the complexity of tax avoidance and emphasize the need for a more holistic approach in tax policy enforcement.